Faktor Yang Berhubungan dengan Tindakan Kepatuhaan Perawat dalam Melakukan Hand Hygiene di RSUD Dr. H. Mohamad Rabain Tahun 2023 - Mayarianti; Ekawati, Dianita; Dwi Priyatno, Akhmad; Harokan, Ali (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Health Care Associated Infections (HAIs) are infections that occur in patients during treatment in hospitals and other health care facilities where there is no infection and is not in the incubation period, including infections in the hospital but appear after the patient returning home, as well as infections due to work for hospital staff and health workers related to the process of health services in health care facilities, the high rate of HAIs in Indonesia can be identified through the low rate of hand hygiene compliance by health workers in health facilities. This research is a quantitative descriptive. The design in this study was an analytic survey with a cross-sectional design. In a cross-sectional design (cross-sectional) researchers will look at the factors that influence nurse compliance in performing hand hygiene, observation or data collection is carried out all at once (point-in-time approach). The number of nurses is 43 people. The selection of nurses as a population is due to when the patient is in the inpatient room. The results showed that the variables of compliance, age, gender, employment status, knowledge, attitudes, availability of facilities, and the role of the Infection Control and Prevention Team (PPI) and the most dominant variables related to nurse compliance in performing hand hygiene at RSUD Dr. H. Mohamad Rabain in 2023 is an attitude (p= 0.012; OR= 12.987). It is recommended to RSUD Dr. H. Mohamad Rabain to improve the field of health services on nurse compliance with related indicators such as employment status, knowledge, attitudes, availability of facilities and the role of the Infection Control and Prevention team (PPI), especially on attitude indicators.